Analysis of Fiqih Textbooks for Madrasah Aliyah Grade X : A Contextual Learning Review - Abd Muis; Mursalim Mursalim (IJIE International Journal of Islamic Education, 2023)
Improving education quality is a crucial policy in Indonesia, yet Fiqh education in Madrasah Aliyah faces challenges due to potentially unengaging teaching methods. Textbooks play a pivotal role as the primary source of knowledge. This study evaluates the appropriateness of the Class X Fiqh Textbook in the context of contextual learning, aligning teaching material with real-world scenarios for practical student connections. The article specifically focuses on analyzing Class X Fiqh Textbooks in the context of contextual learning. This exploratory and descriptive study uses checklists and documentation to analyze data, incorporating theoretical insights from literature studies. The findings reveal the absence of the constructivism element, the presence of standardized procedural topics like Hajj, Umrah, Qurban, and Aqiqah, and predominantly conceptual material in discussions about wealth ownership release, usury, banks, and insurance. Consequently, students acquire knowledge without a genuine understanding of the content. The findings reveal a deficiency in constructivism within Grade X Fikih teaching materials, particularly in conceptual areas like asset ownership transfer, usury, banks, and insurance. Procedural content related to Hajj and Umrah, Qurban, and Akikah is already standardized. This gap may lead to students acquiring knowledge without a thorough understanding. To enhance comprehension, adjustments or additional constructivist elements are essential in the learning process.